Directed evolution as an approach to increase fructose utilization in synthetic grape juice by wine yeast AWRI 796. Issue 1 (26th April 2022) - Walker, Michelle E; Watson, Tommaso L; Large, Christopher R L; Berkovich, Yan; Lang, Tom A; Dunham, Maitreya J; Formby, Sean; Jiranek, Vladimir
Abstract: In winemaking, slow or stuck alcoholic fermentation can impact processing efficiency and wine quality. Residual fructose in the later stages of fermentation can leave the wine 'out of specification' unless removed, which requires reinoculation or use of a more fructophilic yeast. As such, robust, fermentation efficient strains are still highly desirable to reduce this risk. We report on a combined EMS mutagenesis and Directed Evolution (DE) approach as a 'proof of concept' to improve fructose utilization and decrease fermentation duration. One evolved isolate, Tee 9, was evaluated against the parent, AWRI 796 in defined medium (CDGJM) and Semillon juice. Interestingly, Tee 9 exhibited improved fermentation in CDGJM at several nitrogen contents, but not in juice. Genomic comparison between AWRI 796 and Tee 9 identified 371 mutations, but no chromosomal copy number variation. A total of 95 noncoding and 276 coding mutations were identified in 297 genes (180 of which encode proteins with one or more substitutions). Whilst introduction of two of these, Gid7 (E726K) or Fba1 (G135S), into AWRI 796 did not lead to the fermentation improvement seen in Tee 9, similar allelic swaps with the other mutations are needed to understand Tee 9's adaption to CDGJM. Furthermore, the 378 isolates, potentially mutagenized but with the same genetic background, are likely a useful resource for future phenotyping and genome-wide association studies. Abstract : Chemical mutagenesis and directed evolution as an approach to improve fructose utilization during wine fermentation.